Arachne $1 (BVolume 08s - Ebers, Georg, 1837-1898; Safford, Mary J. (Mary Joanna), 1842-1916 (Salt Lake City, UT : Project Gutenberg, 2004)
"Arachne $1 (BVolume 08" by Georg Ebers is a historical novel written during the late 19th century. It weaves a narrative set in ancient times, likely in the context of Hellenistic Egypt, featuring characters immersed in a rich tapestry of artistry, ambition, and personal turmoil. The story revolves predominantly around Hermon, a sculptor who grapples with loss, recovery, and the consequences of love. The opening of the book introduces Hermon as he navigates the emotional landscape of his partially recovered sight and his interactions with Bias, his freedman. Hermon is filled with longing and hope as he receives news of his loved ones. The narrative hints at his past struggles, including his blindness and the tumultuous impact of a woman named Ledscha on his life. As he learns about the developments involving his friends and loved ones, Hermon$1 (Bs thoughts are laden with deep emotional significance, laying the groundwork for a tale that explores themes of artistry, love, vengeance, and redemption against a backdrop of political intrigue and personal ambition. (This is an automatically generated summary.)s
Release date is 2004-04-01
This eBook was produced by David Widger
Keywords: Egypt -- History -- 332-30 B.C. -- Fiction; German fiction -- Translations into English